Sources of Volunteer Motivation: Transformational Leadership and Personal Motives Influence Volunteer Outcomes. Issue 2 (27th August 2013) - Dwyer, Patrick C.; Bono, Joyce E.; Snyder, Mark; Nov, Oded; Berson, Yair
Abstract We examined the separate influences of volunteers' personal motives and their team leaders' behaviors on volunteer satisfaction and contributions, along with mediating processes suggested by self‐determination theory. Participants were 302 volunteers who worked in teams at various sites through a central agency. As predicted, both personal motives for volunteering and transformational leadership influenced volunteer satisfaction through enhanced work meaningfulness and higher‐quality team relationships. However, motives that predicted volunteer contribution were different from those that predicted satisfaction. Whereas satisfaction was positively associated with motives concerning esteem enhancement and value expression, contribution was positively associated with motives to gain understanding and negatively related to motives pertaining to esteem enhancement and social concerns. Transformational leadership was positively associated with volunteer satisfaction, but not with volunteer contributions. The theoretical ramifications of these findings are discussed, along with practical implications for the recruitment and retention of volunteers.